A Partnership Approach to Promoting Information Literacy for Higher Education Researchers - Goldstein, Stéphane (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The promotion of information literacy in the UK higher education research sector has traditionally been the preserve of academic libraries. However, other professional groups have obvious interests in this area, and there is a strong case for providing a framework which enables different parties with a stake in information literacy to work together in order to reach practical objectives. In the UK, a coalition of partners has been set up to provide this collective framework and to provide synergy. This paper sets out the rationale for this approach, sets out the sort of activities that the coalition has fostered since its inception in late 2009 and reflects on whether it might serve as an example for other parts of Europe or for transnational collaborations.